Issues in Teaching English Speaking Skill in Second Language Acquisition (SLA) at Secondary Level - Robina Shaukat; Muhammad Shahbaz Arif; Hina Mangi (CV. Literasi Indonesia, 2020)
This research has investigated the issues in teaching English-speaking skills as second language acquisition SLA, especially in Punjab. It is observed that issues involved in teaching speaking skills by the concerned teachers were having a traditional approach in teaching methodologies, their strict inflexible attitude, and denying attending refresher courses and workshops in modern e-learning enhancement. It has been observed that the teachers occupying permanent seats are least bothered to cope with fresh, young, junior colleagues and institutional management authorities in the practical application of modern latest teaching techniques to produce quality in teaching English as SLA in speaking skills. Qualitative and quantitative methods were applied to find out the objectives in teaching English as SLA in speaking skills. The niche, objective, and aim of the research is to find out practical issues in teaching English as SLA in applied speaking skill and how speaking’ skill could effectively promote language fluency to meet the requirements of the present modern era. This paper declared that the Latest, modern methodologies may be adopted by teachers to produce quality in learning English speaking as SLA in a friendly and pleasant atmosphere in light.